Synergistic Antiproliferative Effects of Combined γ-Tocotrienol and PPARγ Antagonist Treatment Are Mediated through PPARγ-Independent Mechanisms in Breast Cancer Cells - Abhita Malaviya; Paul W. Sylvester (PPAR Research)
Previous findings showed that the anticancer effects of combined γ-tocotrienol and peroxisome proliferator activated receptor γ (PPARγ) antagonist treatment caused a large reduction in PPARγ expression. However, other studies suggest that the antiproliferative effects of γ-tocotrienol and/or PPARγ antagonists are mediated, at least in part, through PPARγ-independent mechanism(s). Studies were conducted to characterize the role of PPARγ in mediating the effects of combined treatment of γ-tocotrienol with PPARγ agonists or antagonists on the growth of PPARγ negative +SA mammary cells and PPARγ-positive and PPARγ-silenced MCF-7 and MDA-MB-231 breast cancer cells. Combined treatment of γ-tocotrienol with PPARγ antagonist decreased, while combined treatment of γ-tocotrienol with PPARγ agonist increased, growth of all cancer cells. However, treatment with high doses of 15d-PGJ2, an endogenous natural ligand for PPARγ, had no effect on cancer cell growth. Western blot and qRT-PCR studies showed that the growth inhibitory effects of combined γ-tocotrienol and PPARγ antagonist treatment decreased cyclooxygenase (COX-2), prostaglandin synthase (PGDS), and prostaglandin D2 (PGD2) synthesis. In conclusion, the anticancer effects of combined γ-tocotrienol and PPARγ antagonists treatment in PPARγ negative/silenced breast cancer cells are mediated through PPARγ-independent mechanisms that are associated with a downregulation in COX-2, PGDS, and PGD2 synthesis.